2019
DOI: 10.1186/s13244-019-0737-3
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the use of the breast lesion excision system in breast disease

Abstract: Purpose To outline the current status of and provide insight into possible future research on the breast lesion excision system (BLES) as a diagnostic and therapeutic device. Methods A systematic search of the literature was performed using PubMed, Embase, and the Cochrane databases to identify relevant studies published between January 2002 and April 2018. Studies were considered eligible for inclusion if they evaluated the diagnostic or therapeutic accuracy or safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(106 reference statements)
1
4
0
Order By: Relevance
“…Previous studies report device-related complications comparable to ours using BLES, of which empty basket is the most common [22]. Thermal artifact is another device-related problem with BLES but it is unlikely to affect the histopathological analysis [22]. These device-related complications do not occur in VAE procedures.…”
Section: Complications and Riskssupporting
confidence: 66%
“…Previous studies report device-related complications comparable to ours using BLES, of which empty basket is the most common [22]. Thermal artifact is another device-related problem with BLES but it is unlikely to affect the histopathological analysis [22]. These device-related complications do not occur in VAE procedures.…”
Section: Complications and Riskssupporting
confidence: 66%
“…There was only one case where an empty basket was retrieved. According to the relevant literature, the relative frequency of such an event is 0.6–3.6% [ 12 ]. Such cases are usually due to the failure of the basket to deploy or to the presence of a very tight entry point or access path.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, this rate was found to be 40%, although the number of malignant cases was too low to reach a solid conclusion regarding this parameter. The large variation in the literature regarding the rate of complete excision raises some questions about the use of BLES as a therapeutic device [ 12 , 14 ]. However, it is not uncommon for patients to undergo more than one surgical procedure before achieving tumor-free margin even in surgery [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, percutaneous image-guided systems aiming to completely remove small breast lesions have been developed [49][50][51], for instance using radiofrequency to excise intact lesions in a basket preserving the tissue structure [52][53][54][55]. These devices have the potential to provide highly accurate tissue diagnosis and offer an alternative option for percutaneous lesion removal.…”
Section: Other Breast Biopsy Systemsmentioning
confidence: 99%